Respuesta :

The equivalent expression is -12y + 48 or -12(y - 4) or 12(-y + 4)

Solution:

Given that we have to simplify to create an equivalent expression

Given expression is:

6(7 – 3y) + 6(y + 1)

Remove the parenthesis by multiplying terms inside the bracket with constant outside the bracket

[tex]\rightarrow 6(7 - 3y) + 6(y + 1)\\\\\rightarrow 42 - 18y + 6y + 6[/tex]

Combine the like terms

[tex]\rightarrow -12y + 42 + 6[/tex]

Add the constants

[tex]\rightarrow -12y + 48[/tex]

Thus the equivalent expression is -12y + 48 or -12(y - 4) or 12(-y + 4)